Poverty, Environmental Degradation And Sustainable Development: A Discourse (Global Journal of Human-Social Science, 2012)
This paper is a contribution to the ongoing debate on the topical issues of poverty environmental degradation and sustainable development by highlighting the divergent views and attempting an explanation of the diversity Poring through the literature the authors observed that there are three discernable debaters on the trajectory between poverty environmental degradation and sustainable development namely those who argue that the poor the South is the major cause of environmental degradation as a result of high population and increased pressure on environmental resources those who contend that the high consumption propensity of the rich the North is the main factor in environmental degradation and those who argue that both the rich and the poor in varying capacities contribute to the unsustainability of the environment The authors believe that quantitative data are required to ascertain whether the poor South more than the rich North degrade the environment or not Until such evidence is found the North-South dichotomy on ecological issues will persist One common thread that runs through the various views is that there is continued degradation of the environment the negative impact of which affects both the poor and the rich As such the quest for sustainable development should be utmost concern of all
Keywords: Poverty; environmental degradation; sustainable development; north-south dichotomy; debtresource hypothesis